Earnings Management Using Classification Shifting: An Examination of Core Earnings and Special Items - McVay, Sarah Elizabeth (The Accounting Review, 2006)
This paper examines the classification of items within the income statement as an earnings management tool. Evidence is consistent with managers opportunistically shifting expenses from core expenses (cost of goods sold and selling, general, and administrative expenses) to special items. This vertical movement of expenses does not change bottom-line earnings, but overstates “core” earnings. In addition, it appears that managers use this earnings management tool to meet the analyst forecast earnings benchmark, as special items tend to be excluded from both pro forma and analyst earnings definitions.